SUGGESTED IMPROVEMENTS IN GOVERNMENTAL ACCOUNTING. - Lorig, Arthur N. (The Accounting Review, 1963)
Abstract The article presents suggestions by the author for improvements in governmental accounting. The author suggests that the accounting staff should be alert to possible savings in costs and improvements in its accounting and reporting, it should even be ready to eliminate procedures if the resulting information is not worth the time and cost necessary to obtain it. Even the recommendations of authoritative accounting bodies should not be followed blindly, it is always appropriate and wise to seek to know why a procedure should be followed. It is possible that a procedure useful to many governments may not be advantageous to others. Accuracy is also significant. If information being presented to management and the public turns out to be inaccurate or misleading, the accountant is obligated to correct the presentation. Government accountants should constantly look at their work critically and realistically and be every ready to make changes where improved results or efficiency would follow.